Cracks on ETICS along thermal insulation joints: case study and a pathology catalogue. Issue 1 (11th April 2016) - Freitas, Sara Stingl de; de Freitas, Vasco Peixoto
Abstract : Purpose: – The purpose of this paper is to present a case study of cracks on external thermal insulation composite systems (ETICS) along the thermal insulation joints and the information available on the building pathology catalogue – PATORREB. The aim is to establish the methodology to study the cause of the pathology observed on a building which is located on the interior of Portugal based on in situ probing together with the analysis of hygrothermal and mechanical behaviour. Design/methodology/approach: – An in situ analysis was performed to assess the causes. The hygrothermal dynamic behaviour of the wall was analysed with a numerical simulation advanced tool considering the climatic conditions, the characteristics of the thermal insulation plates as well as the support and finishing layer properties. Moreover, a qualitatively analysis of the mechanical behaviour, based on the bonding process, thermal insulation and exterior rendering properties was performed. Findings: – It was concluded that the insulation properties – thermal expansion coefficient and stiffness, the thermal expansion coefficient of the exterior rendering, together with adverse climatic conditions were critical for the appearance of cracks along the plate joints, particularly with spot bonding. The expansion and retraction stresses and the restrained movements of the components can result in bending moments, especially when the insulation material has a high stiffness value, which will create the crack on the rendering system. Originality/value: – A combination between a hygrothermal and mechanical analysis of an ETICS pathology concerning the appearance of cracks with a subsequent integration into a building pathology catalogue.